2009
DOI: 10.1007/bf03218608
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of novel flame-retardant and thermally stable poly(amideimide) s fromN,N′-(bicyclo[2,2,2]oct-7-ene-tetracarboxylic)-bis-L-amino acids and phosphine oxide moiety by two different methods

Abstract: N,N'-(bicyclo[2,2,2]oct-7-ene-tetracarboxylic)-bis-L-amino acids 3a-g were synthesized by the condensation reaction of bicyclo[2,2,2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride 1 with two equimolars of Lalanine 2a, L-valine 2b, L-leucine 2c, L-isoleucine 2d, L-phenyl alanine 2e, L-2-aminobutyric acid 2f and L-histidine 2g in an acetic acid solution. Seven new poly(amide-imide)s PAIs 5a-g were synthesized through the direct polycondensation reaction of seven chiral N,N'-(bicyclo[2,2,2]oct-7-ene-tetracarboxyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…All the PEIs had LOI values calculated based on their char yield were higher than 23.1 (Table 3). The LOI values are comparable with the flame-retardant and thermally stable poly(amide-imide)s reported by Faghihi et al 26 All the samples of the present study can be used as flame-retardant materials. The LOI for the PEI-1 was low due to the presence of aliphatic moiety that is sensitive to heat, while the LOI value was high for PEI-4 due to para catenation of the phenyl group which led to compact network structure.…”
Section: Limiting Oxygen Indexsupporting
confidence: 90%
“…All the PEIs had LOI values calculated based on their char yield were higher than 23.1 (Table 3). The LOI values are comparable with the flame-retardant and thermally stable poly(amide-imide)s reported by Faghihi et al 26 All the samples of the present study can be used as flame-retardant materials. The LOI for the PEI-1 was low due to the presence of aliphatic moiety that is sensitive to heat, while the LOI value was high for PEI-4 due to para catenation of the phenyl group which led to compact network structure.…”
Section: Limiting Oxygen Indexsupporting
confidence: 90%
“…Many studies have shown that polymers containing phosphorus functional groups, such as phosphonate, 10 phosphinate 11 or phosphine oxide groups, 12 can improve the flame retardancy, solubility and adhesion to metal oxides and metal hydroxides 13 . Many phosphorus‐containing monomers have been proposed for the synthesis of flame‐retardant polymers, such as polyamides with some improved essential properties such as solubility in organic solvents, thermal stability and combustion resistance 14–19 …”
Section: Introductionmentioning
confidence: 99%
“…Hence, the introduction of sulfur-containing groups (S¼O and C¼S) was found to increase the nonflammability of the polymers without reducing their thermal stability. The polyazos were found to be sufficiently nonflammable relative to the previous polymers 29 and exhibited higher LOI value for PASA 1, as in the case of their thermal stability (Table 3). The results showed that the presence of sulfone, thiourea and azobenzene moieties in the main chain dramatically increased the flame-retardant property of these polymers.…”
Section: Thermal Stabilitymentioning
confidence: 90%